Demography, education, and research trends in the interdisciplinary field of disease ecology. Issue 24 (14th December 2021) - Brandell, Ellen E.; Becker, Daniel J.; Sampson, Laura; Forbes, Kristian M.
Abstract: Micro‐ and macroparasites are a leading cause of mortality for humans, animals, and plants, and there is great need to understand their origins, transmission dynamics, and impacts. Disease ecology formed as an interdisciplinary field in the 1970s to fill this need and has recently rapidly grown in size and influence. Because interdisciplinary fields integrate diverse scientific expertise and training experiences, understanding their composition and research priorities is often difficult. Here, for the first time, we quantify the composition and educational experiences of a subset of disease ecology practitioners and identify topical trends in published research. We combined a large survey of self‐declared disease ecologists with a literature synthesis involving machine‐learning topic detection of over 18, 500 disease ecology research articles. The number of graduate degrees earned by disease ecology practitioners has grown dramatically since the early 2000s. Similar to other science fields, we show that practitioners in disease ecology have diversified in the last decade in terms of gender identity and institution, with weaker diversification in race and ethnicity. Topic detection analysis revealed how the frequency of publications on certain topics has declined (e.g., HIV, serology), increased (e.g., the dilution effect, infectious disease in bats), remained relatively common (e.g., malaria ecology, influenza, vaccine research and development), or have consistently remained relatively infrequent (e.g., theoretical models, field experiments). Other topics, such as climate change, superspreading, emerging infectious diseases, and network analyses, have recently come to prominence. This study helps identify the major themes of disease ecology and demonstrates how publication frequency corresponds to emergent health and environmental threats. More broadly, our approach provides a framework to examine the composition and publication trends of other major research fields that cross traditional disciplinary boundaries. Abstract : Here, we describe the composition and research trends in the growing field of disease ecology using a large survey and powerful literature synthesis. Disease ecology practitioners are more diverse in terms of gender, but less so in terms of race and ethnicity and country of research. Research trends have followed global disease events (e.g., SARS), with some foci increasing in publication frequency (e.g., the dilution effect, superspreading), some decreasing (e.g., HIV), and some remaining stable and prominent (e.g., influenza, malaria).